The Influence of System Quality, Information Quality, and Service Quality on User Satisfaction of the M-Passport Application at the Class I TPI Bandar Lampung Immigration Office - Putri Rachma Sholeha; Yulianto, Yulianto; Ahmad Rifa’i (International Journal of Economics, Business and Innovation Research, 2025)
In today's digital era, information technology plays an important role in improving the quality of public services. One of the innovations implemented by the Class I TPI Bandar Lampung Immigration Office is the use of the M-Passport application to facilitate the online passport application process. This study aims to analyze the effect of system quality, information quality, and service quality on the satisfaction of M-Passport application users at the Class I TPI Bandar Lampung Immigration Office. The method used in this study is a survey with a quantitative approach. Specifically, system quality has a strong influence on user satisfaction, followed by information quality and service quality. Positive assessments of system quality, information, and service indicate that the M-Passport application has met user needs in terms of reliability, ease of use, and response speed. Thus, this study concludes that in order to improve user satisfaction of the M-Passport application, the Class I TPI Bandar Lampung Immigration Office needs to continue to improve the quality of the system, information, and services provided. This study is expected to provide insight for M-Passport application managers and related agencies in efforts to improve public services based on information technology.